Indigenous potential ornamental flowering plants of Himachal Pradesh - Chandra, A; Verma, P K; Thakur, Priyanka; Joshi, A K (Indian Horticulture, 2019)
Himachal Pradesh has 66% of the total geographical area as recorded forest area. Varying climatic and adaphic conditions have resulted in rich plant diversity in the state. One of the prospective uses of floristic diversity is the aesthetic value which can be utilized for the livelihood generation in the rural areas. Number of studies have been made to document the floristic wealth of the state. However, potential value wild plants species for ornamental purpose are not aptly highlighted. Therefore, in this article an endeavour has been made to list out potential wild plant species which can be exploited for ornamental purpose in near future. Different aspects of these wild plants should be thoroughly studied for their suitability as commercial ornamental crop.